Real-Time Local Optimal Bézier Corner Smoothing for CNC Machine Tools - Tzyy-Chyang Lu (IEEE, 2021)
A straight line or G01 is the most common path in computer numerical control (CNC) contour machining. However, non-smooth corners introduce discontinuous movement along each axis during machining. The commonly used strategy is to redesign a corner into a smooth corner path. Therefore, optimal corner smoothing should simultaneously find an optimal corner path and a corner speed that satisfied the axis motion limits. To achieve this goal, we use particle swarm optimization (PSO) to find the optimal Bézier curve and the optimal corner speed, then convert the axis constraints into polynomial inequalities and use fitness selection to deal with axis acceleration and jerk limits. For real-time operation, we establish a look-up table with the optimal corner speed and corner path models for use by a CNC controller. In the experiment, the YCM NXV560A vertical machining center was used to conduct a real machining test on a Taiwan contour, and the feasibility of the controller to generate the optimal corner strategy for various linear paths was verified.